Correlation of Law and Order in Society - Valiev, Gabdrakhman H.; Kondratyuk, Sergey V.; Prodanova, Natalia A.; Babalikova, Irina A.; Makaeva, Kermen I.; Baishev, Innokentiy I. (Cuestiones Políticas, 2020)
The problem of the relationship of law and order is relevant to any modern society. The article tries to analyze this relationship, taking into account judicial, police and other activities. The named concepts are closely interconnected, but are not identical. They are correlated as cause and effect: there is a rule of law, there is no rule of law. One suggests the other. The rule of law as concrete reality logically precedes the rule of law as a doctrine, the connection here is hard, causal. The process is one. Law and order: a real indicator of the state of legality, reflects the degree of compliance with the laws, the requirements of all legal regulations. It is concluded that the rule of law is the end result of the implementation of legal requirements and, at the same time, the objective of legal regulation, since it is for the formation and maintenance of the rule of law that laws are issued, thus like other regulatory legal acts, various institutions and bodies and, above all, the justice system, the control system, various human rights organizations and social movements.